Determination of Correlation and Relative Intensity Noise of the Chaos and the Message Masked by the Chaos - Chanagala, Satyanarayana; Kanduri, Madhu Sudhana Rao (New Approaches in Engineering Research Vol. 15, 2021)
With correlation and Relative Intensity Noise analysis, the potential of secure communication utilizing Chaos is demonstrated analytically in this work. The auto-correlation coefficients in pure chaos reveal randomness, and a correlation coefficient displays a decaying periodic behavior for the message, which in this case is a sinusoidal signal. Extensive research is being undertaken in using chaos: both optical and electronic forms, as a via media for secure communications. The correlation coefficient for continuous time delay data and its dependence on time delay is calculated using the ORIGIN software. Both efficiently encoded and inefficiently encoded signals have their RIN determined. The RIN for an efficiently encoded message is higher than for an inefficiently encoded message. This underlines the idea that chaos may be a powerful tool for secure communication.